Investigating relationships between women's moods and their menstrual cycles - a multimethod study - Sieberhagen, Stephanie (Department of Psychiatry and Mental Health, 2019)
A multi-method study was conducted to investigate the relationships between a woman’s menstrual-cycle and her moods. Twenty eight participants were recruited using convenience sampling. Each participant provided data for two full menstrual cycles by taking part in a pre and post-study in-depth interview; answering a structured daily self-report diary utilising a Likert scale and completing three established research instruments – the Brunel Scale of Moods, the Menstrual Distress Questionnaire and the Born-Steiner Irritability Questionnaire, weekly. Interviews were conducted in person and quantitative data were collected electronically via e-mail. The mixed-methods methodology resulted in quantitative data that were analysed using STATA statistical software and the ecological multivariate data analysis software package known as PRIMER. Results from the statistical software were represented graphically and indicated that there is a relationship between menstrual cycle days and moods, with individual women’s correlations differing from each other to some extent. The data confirmed that there are groups of women who follow a very similar mood pattern and that educational level, vocation, exercise and participation in volunteer work or hobbies defines these groups to some degree. The qualitative data supported these findings and indicated the impact of menstrual cycle related moods on women’s daily functioning. The study concludes that menstrual cycle related moods play a role in overall life satisfaction and that psycho education and awareness can improve overall quality of life.